A comparative study of highly underexpanded nitrogen and hydrogen jets using large eddy simulation. (9th March 2016) - Li, Xiaopeng; Wu, Kun; Yao, Wei; Fan, Xuejun
Abstract: Three-dimensional large eddy simulations (LES) of highly underexpanded hydrogen and nitrogen jets at the same nozzle pressure ratio (NPR) of 5.60 and at a Reynolds number around 10 5 are performed. The classical near-field structures of highly underexpanded jets are well captured by LES, especially the shape and size of Mach barrel for both jets are very similar and agree well with the available literature data. However, the flow field and the shock structures after the Mach disk differ significantly. The density in the annular shear layer of H2 jet is much lower because of its smaller molecular weight. Meanwhile, the H2 jet has a much longer jet core and more shock cells. The dominant instability mode is helical for the N2 jet, but is axisymmetric for the H2 jet. There are two discrete peaks of f s  = 37.086 kHz and f 2s  = 45.695 kHz in the spectrum of the N2 jet, while the spectrum of the H2 jet is characterized by a fundamental screech frequency of f s  = 47.020 kHz and its high-order harmonics. The H2 jet mixes more rapidly with the ambient air but has a much smaller mixing area on cross-section planes. Mixing between the ambient air and fuel still takes places at the jet boundary defined according to the mixture fraction of Z = 0.02, and the area of fully turbulent region of the highly underexpanded jets seems to be less predicted based on the traditional vorticity T/NT (turbulent/non-turbulent) interface for both jets. Highlights: Three-dimension LES modeling is performed to study a highly underexpanded H2 jet in comparison with N2 jet at same NPR. The structure of Mach barrel predicted agrees well with available data. The density in H2 jet is lower, and H2 jet also has longer jet core and more shock cells. The dominant instability mode is helical for N2 jet, but axisymmetric for H2 jet. H2 jet mixes more rapidly with air but has smaller mixing area on cross-section planes.